2016
DOI: 10.1037/fsh0000219
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ integration in the treatment of adolescents with obesity: A qualitative study.

Abstract: Family dynamics are an important issue in weight-loss treatment during adolescence. Including both parents and adolescents in therapy is crucial for tackling obesity and addressing health needs related to this age group. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 48 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…Adolescents were encourage to bring a friend to [one] session, and friends were integrated into the activities [ 71 ] [ 29 , 33 , 35 40 , 42 , 43 , 47 , 49 , 50 , 56 , 60 63 , 70 72 ] The Youth Quality of Life (YQOL) Inventory, including a social relationship subscale [ 49 ] The Support for Exercise Scale (revised version) [ 56 ] The Social Support for Eating Habits and Exercise Scale [ 61 ] Parent Relationship with Peer Group Scale [ 33 ] Family Functioning Family member roles and interactions that affect day-to-day living within the home environment, including acceptance and understanding of one another, family decision-making and problem-solving processes, and general communication among family members. Simply described as the overall healthiness of a family unit 10 Multidisciplinary FBBT : Nutrition-related topics and systemic interventions to facilitate family functioning by reinforcing family resources and improving the emotional climate for adolescents with obesity [ 57 ] [ 30 , 31 , 33 , 35 40 , 47 , 56 , 57 , 60 , 64 , 70 72 ] The Self-Report Family Inventory (SFI), including the conflict resolution, cohesion, and family nurturance subscales [ 60 ] The Family Adaptability and Cohesion Evaluation Scales IV (FACES IV) [ 67 , 68 ] The Family Climate Scale [ 72 ] Family Questionnaire (FQ) [ …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adolescents were encourage to bring a friend to [one] session, and friends were integrated into the activities [ 71 ] [ 29 , 33 , 35 40 , 42 , 43 , 47 , 49 , 50 , 56 , 60 63 , 70 72 ] The Youth Quality of Life (YQOL) Inventory, including a social relationship subscale [ 49 ] The Support for Exercise Scale (revised version) [ 56 ] The Social Support for Eating Habits and Exercise Scale [ 61 ] Parent Relationship with Peer Group Scale [ 33 ] Family Functioning Family member roles and interactions that affect day-to-day living within the home environment, including acceptance and understanding of one another, family decision-making and problem-solving processes, and general communication among family members. Simply described as the overall healthiness of a family unit 10 Multidisciplinary FBBT : Nutrition-related topics and systemic interventions to facilitate family functioning by reinforcing family resources and improving the emotional climate for adolescents with obesity [ 57 ] [ 30 , 31 , 33 , 35 40 , 47 , 56 , 57 , 60 , 64 , 70 72 ] The Self-Report Family Inventory (SFI), including the conflict resolution, cohesion, and family nurturance subscales [ 60 ] The Family Adaptability and Cohesion Evaluation Scales IV (FACES IV) [ 67 , 68 ] The Family Climate Scale [ 72 ] Family Questionnaire (FQ) [ …”
Section: Resultsmentioning
confidence: 99%
“…Inconsistency in results may be due to the relatively low number of studies that measured FST-related variables. Some studies used qualitative methods to assess participants’ perspectives on changes in the family system following the intervention, both of which reported perceived improvements [ 36 , 57 ]. Qualitative exploration may allow for a deeper understanding of family beliefs associated with family system concepts at baseline and how these evolve following an intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Few fathers participated alongside their children. Two studies reported that fathers were difficult to recruit (Bishop et al, 2015;Chamay Weber et al, 2016). Underrepresentation of fathers may skew results, as fathers'perceptions and views may differ from those of mothers.…”
Section: Discussionmentioning
confidence: 99%
“…While it is common for adolescents to struggle with becoming independent and to wish to escape from their parents' control, study participants voiced that the constant control their parents exerted on their eating habits discouraged them. In Chamay Weber et al (2016), a 15-year-old girl said that her mother was always watching her and checking everything she ate, and that her mother did not understand that she could cope by herself. The adolescents were torn between their perceived inability to control their food intake, which was worsened by the constant monitoring of their parents, and their desire for responsibility and autonomy.…”
Section: Issues Reported By Children and Adolescentsmentioning
confidence: 99%
See 1 more Smart Citation